2001
DOI: 10.1067/mva.2001.115802
|View full text |Cite
|
Sign up to set email alerts
|

Late recurrent saphenofemoral junction reflux after ligation and stripping of the greater saphenous vein

Abstract: This 34-year clinical follow-up study shows a 60% incidence of junctional and circumjunctional reconnections after ligation of the true saphenofemoral junction and its related tributaries. Color-coded duplex sonography is a necessary concomitant to clinical examination, detecting more recurrences and defining the pathologic anatomy to direct clinically indicated additional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
145
0
20

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 10 publications
1
145
0
20
Order By: Relevance
“…Vein ligation without stripping achieved only 58% freedom from reflux at 2 years, and only 29% freedom from reflux at 5 years. Fischer and colleagues [43] studied 125 limbs after ligation of the true saphenofemoral junction and its related tributaries, and found that 60% of limbs had SFJ reflux at mean follow-up of 3.4 years.…”
Section: Endovenous Radiofrequency Ablation Versus Vein Strippingmentioning
confidence: 99%
“…Vein ligation without stripping achieved only 58% freedom from reflux at 2 years, and only 29% freedom from reflux at 5 years. Fischer and colleagues [43] studied 125 limbs after ligation of the true saphenofemoral junction and its related tributaries, and found that 60% of limbs had SFJ reflux at mean follow-up of 3.4 years.…”
Section: Endovenous Radiofrequency Ablation Versus Vein Strippingmentioning
confidence: 99%
“…Other authors agree that recurrent varicose vein surgeries make 20% of all the procedures relating to lower limbs (2,10,11). Their costs are enormous.…”
Section: Discussionmentioning
confidence: 99%
“…The data from available literature show that recurrent varicose veins arise from persistent reflux in saphenous vein or in the area of saphenofemoral junction (2,6,7,8). Most often, pathologic regressive blood flow appears in peripheral vessels which were overlooked during the primary surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the clinical features assessed as per VCSS correlated well with the disability caused by varicose veins in lower limbs, assessed using the VDS. 12 et al found that the surgery was reasonable definitive therapy of primary varices, but secondary varices usually require rest, elevation and elastic support.…”
Section: Agementioning
confidence: 99%